Improvement of the feed system of the coal combine by means of load forecasting - Зубарев, Сергей Геннадьевич (Technology audit and production reserves, 2014)
This article presents the consideration of the methods of increasing effectiveness of protection against overloads of electric drives and executive bodies of the booty combine with outrigger feed system. The main purpose of the study is validation the ways to improve efficiency protection against sudden overloads and improving the dynamic properties of the outrigger feed system. It is developed a computer simulation of transient processes in outrigger feed system and it is shown the process of formation of dynamic overloads on the executive bodies of the booty combine. It is justified ways of improving transient towards decrease dynamic overloads. For this purpose it is proposed the use of preliminary smooth decrease feed rate before the abrupt change of the mechanical properties of the mine for a period of 2 to 5 seconds. Further research may focus on the justification of the methods of analysis of the mechanical properties of the mine and the parameters of the system software load control combine with outrigger feed system.